Transactional capability: Innovation's missing link - Tello Gamarra,Jorge (2013)
The topic of innovation as a source of competitive advantage for firms is consolidated in the literature. An innovation-based advantage is generally achieved by following a structured process, in which technological capability plays a key role. However, a question remains in studies into innovation, which is concerned with the reasons why not all firms that develop a technological capability are innovative. Where is the missing link? Great efforts have been made in attempts to answer to this question. However, the study of this link as a source of advantage for firms deserves further attention. This article aims to present a framework with two essential dimensions: (1) the technological capability and (2) the transactional capability. Technological capability is the ability of firms to make effective use of technical knowledge in order to improve production processes and develop new products and services. Transactional capability is defined as a repertoire of abilities, processes, experiences, skills, knowledge and routines that the firm uses to minimize its transaction costs (ex-ante and ex-post). Given that the present study is a theoretical paper, methodologically it is based on a literature review. The main finding of this study is the identification of transactional capability as the missing link in innovation. Accordingly, to be innovative, in addition to having a technological capability, a firm needs to develop its transactional capability.